Nanopore MinION Sequencing Reveals Possible Transfer of blaKPC–2 Plasmid Across Bacterial Species in Two Healthcare Facilities - Prussing, Catharine; Snavely, Emily A.; Singh, Navjot; Lapierre, Pascal; Lasek-Nesselquist, Erica; Mitchell, Kara; Haas, Wolfgang; Owsiak, Rita; Nazarian, Elizabeth; Musser, Kimberlee A. (Frontiers in Microbiology, 2020)
Carbapenemase-producing Enterobacteriaceae are a major threat to global public health. Klebsiella pneumoniae carbapenemase (KPC) is the most commonly identified carbapenemase in the U.S. and is frequently found on mobile genetic elements including plasmids, which can be horizontally transmitted between bacteria of the same or different species. Here we describe the results of an epidemiological investigation of KPC-producing bacteria at two healthcare facilities. Using a combination of short-read and long-read whole-genome sequencing, we identified an identical 44 kilobase plasmid carrying the blaKPC-2 gene in four bacterial isolates belonging to three different species (Citrobacter freundii, Klebsiella pneumoniae, and Escherichia coli). The isolates in this investigation were collected from patients who were epidemiologically linked in a region in which KPC was uncommon, suggesting that the antibiotic resistance plasmid was transmitted between these bacterial species. This investigation highlights the importance of long-read sequencing in investigating the relatedness of bacterial plasmids, and in elucidating potential plasmid-mediated outbreaks caused by antibiotic resistant bacteria.